Pemikiran Pendidikan Karakter Al-Ghazali, Lawrence Kolberg dan Thomas Lickona - Mainuddin, Mainuddin; Tobroni, Tobroni; Nurhakim, Moh. (Attadrib: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2023)
This paper aims to find out how Al-Ghazali, Lawrence Kolberg, and Thomas Lichona think about character education in contemporary Islam. The benefits for the government and educators make the educational ideas of Al-Ghazali, Lawrence Kolberg, and Thomas Lichona an inspiration in upholding quality Indonesian education. This research method is qualitative with descriptive analysis techniques using library research (library research). Through this literature review, researchers try to describe existing phenomena, which are currently taking place or in the past, and are sourced from various sources that have theoretical depth from experts. This study examines the perspective of character education according to Al-Ghazali, Thomas Lickona, and Lawrence Kolberg by examining the theories put forward. The results of this paper are that according to Al-Ghazali educational thinking is religious-ethical in nature, al-Ghazali's educational goals cover three aspects, namely cognitive aspects, affective aspects, and psychomotor aspects. Al-Ghazali mentioned four scientific classification categories, namely; classification of science syar'iyah (religion) and 'aqliyah (reason); theoretical and practical sciences; knowledge is presented (hudhûri) and acquired (hushûli); The knowledge of fardhu 'ain and fardhu kifayah. Meanwhile, Thomas Lickona stated that the notion of character education is a deliberate effort to help someone understand, pay attention to, and carry out core ethical values. And more broadly, he stated that character education is a deliberate (conscious) effort to realize virtue, namely objectively good human traits, not only good for individuals but also good for society as a whole. According to Lawrence Kolberg, Kohlberg offers fictional moral issues, so that for the context of the Indonesian nation, it is necessary to prioritize contemporary moral issues that actually occur in everyday life. In this case, what needs to be emphasized is that children have diverse experiences in social problems. Children must also be confronted with moral problems from a different perspective. Thus the diversity of moral problems and various perspectives in solving moral problems will encourage children's moral development to a higher stage.